2020
DOI: 10.1515/epoly-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-catalyzed synthesis and post-polymerization modification of new fully bio-based poly(hexamethylene γ-ketopimelate) and poly(hexamethylene γ-ketopimelate-co-hexamethylene adipate) copolyesters

Abstract: AbstractA novel full bio-based ketone-containing aliphatic polyester was prepared by enzyme-catalyzed polycondensation of diethyl γ-ketopimelate (DEK) with 1,6-hexanediol (HDO) using immobilized lipase B from Candida antarctica (CALB). The influences of polymerization conditions such as temperature, time, enzyme amount, and solvent amount on the molecular weight of poly(hexamethylene γ-ketopimelate) (PHK) were investigated. New fully bio-based poly(he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…EP is known to proceed at generally low temperatures (<100 °C) and has high stereo-/regio-enantio-selectivity, which is particularly promising to minimize the thermal decomposition isohexides, particularly in IM. In recent years, enzyme catalysts have been extensively employed to catalyze different types of monomers toward the synthesis of polyesters, polyamides, and polyesteramides. , CALB has also been employed to synthesize prepolymers or polymers based on other natural compounds of sustainable or renewable sources. In a report published by Wu et al very recently, CALB has shown to be very efficient for synthesizing a novel biobased copolyester based on diethyl γ-ketopimelate, diethyl adipate, and 1,6-hexanediol. The resulting homo-/copolyesters were obtained with fairly high MWs with M n values over 20,000 Da and narrow polydispersities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EP is known to proceed at generally low temperatures (<100 °C) and has high stereo-/regio-enantio-selectivity, which is particularly promising to minimize the thermal decomposition isohexides, particularly in IM. In recent years, enzyme catalysts have been extensively employed to catalyze different types of monomers toward the synthesis of polyesters, polyamides, and polyesteramides. , CALB has also been employed to synthesize prepolymers or polymers based on other natural compounds of sustainable or renewable sources. In a report published by Wu et al very recently, CALB has shown to be very efficient for synthesizing a novel biobased copolyester based on diethyl γ-ketopimelate, diethyl adipate, and 1,6-hexanediol. The resulting homo-/copolyesters were obtained with fairly high MWs with M n values over 20,000 Da and narrow polydispersities.…”
Section: Introductionmentioning
confidence: 99%
“…34−36 In a report published by Wu et al very recently,34 CALB has shown to be very efficient for synthesizing a novel biobased copolyester based on diethyl γ-ketopimelate, diethyl adipate,…”
mentioning
confidence: 99%
“…Numerous types of polymers prepared by enzymatic polymerization have been reported, among them polyphenols by enzymatic oxidative polymerization [3], polyaniline by enzymatic catalysis in presence of hydrogen peroxide [4], polysaccharides [5,6], vinyl polymerizates (being typically chain growth polymerizates) [7], a high number of differ-ent polyesters, polythioesters, polythioetheresters, polyphosphates, or polyketoetheresters obtained by ring-opening polymerization [8][9][10][11] or by polycondensation [12][13][14]. Polyesters and polyamides attracted particular attention, reflected by various studies [1,[15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%